Perancangan Game Stack Jump Rabbit Dengan Menerapkan Algoritma Greedy Berbasis Android - Irwan, Irwan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Games, more commonly known as 'permainan' in Indonesian, are systems with specific rules where players engage in a challenge to produce measurable outcomes, either winning or losing, thus enticing individuals to participate as a form of entertainment. Stack Jump Rabbit game is an arcade platform game utilizing characters to challenge players to jump and land on blocks coming from both sides (right - left) to stack them up, earning points for successful jumps, avoiding block collisions, and building the tallest tower. Greedy Algorithm is one of the most popular methods for solving optimization problems. Stack Jump Rabbit game incorporates the function to find solutions by implementing the greedy algorithm, triggered when jumping within the application. With this greedy algorithm, blocks move until they reach a perfect stacking point, and the function of these blocks is repeatedly called each time a character lands on them.